ORGANIZATIONAL AWARENESS AND MARKETING PREFERENCES OF MEMBERS OF AGRICULTURAL PRODUCER ORGANIZATION: THE CASE OF TURKEY - Uğur SAGLAM; Nizamettin ERBAS; İ. Hakkı İNAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper reviews the organizational awareness and marketing preferences of members of producer organizations in agriculture. The main material of this research consisted of surveys applied to 360 producers determined via the Proportional Sampling Method in Uşak province, Turkey. According to the research results, each of the producers was a member of at least one Producers' Organization (PO). 59.1% of producers were interested in the PO, and 33.6% of them think that crops should be marketed by the Agricultural Development Cooperative. The ratio of member producers marketing their products through the POs was 19.7%. Only 38.4% of members were satisfied with the selling price of products. The POs in the region were generally successful, and the most successful one was also the Agricultural Development Cooperative with 72.3%. In the study, marketing prices, satisfaction with being a member of the POs, and satisfaction with the organizational management variables were tested by the Chi-square, and it was viewed that there was no significant difference among them. The study is important in increasing the effectiveness of the POs in all areas of agriculture and improving the organizational awareness of their members.